Relationship between employee job satisfaction and employees’ loyalty towards the organization - Islam, Md. Tausiful (BRAC Univeristy, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2016.